Surveillance on Healthcare Workers During the First Wave of SARS-CoV-2 Pandemic in Italy: The Experience of a Tertiary Care Pediatric Hospital - Valentina Guarnieri; Valentina Guarnieri; Maria Moriondo; Maria Moriondo; Mattia Giovannini; Mattia Giovannini; Lorenzo Lodi; Lorenzo Lodi; Silvia Ricci; Silvia Ricci; Laura Pisano; Laura Pisano; et al. (Frontiers Media S.A., 2021)
Healthcare workers (HCWs) play a central role in handling the ongoing coronavirus disease 2019 (COVID-19) pandemic. Monitoring HCWs, both symptomatic and asymptomatic, through screening programs, are critical to avoid the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the hospital environment to rapidly identify and isolate infected individuals and to allow their prompt return to work as soon as necessary. We aim to describe our healthcare surveillance experience (April 2-May 6, 2020) based on a combined screening consisting of real-time PCR (RT-PCR) on nasopharyngeal (NP) swabs and rapid serologic tests (RST) for SARS-CoV-2 in all HCWs of Meyer Children's University Hospital in Florence. Among the analyzed workers, 13/1690 (0.8%), all of them without clinical manifestations, was found positive for SARS-CoV-2 by using RT-PCR on NP swab: 8/1472 (0.5%) were found positive during the screening, 1/188 (0.5%) during contact with a positive individual (p > 0.05 vs. screening group), while 4/30 (13.3%) were found positive on the day of re-admission at work after an influenza-like-illness (p < 0.05). Concerning working areas, the majority of RT-PCR positivity (12/13) and serologic positivity (34/42) was found in non-COVID-19 dedicated areas (p > 0.05 vs. COVID-19 dedicated areas). No cases were registered among non-patients-facing workers (p = 0.04 vs. patient-facing group). Nurses and residents represented, respectively, the working role with the highest and lowest percentage of RT-PCR positivity. In conclusion, accurate surveillance is essential to reduce virus spread among HCWs, patients, and the community and to limit the shortage of skilled professionals. The implementation of the surveillance system through an efficient screening program was offered to all professionals, regardless of the presence of clinical manifestations and the level of working exposure risk, maybe wise and relevant.